PENGARUH WORK DEMAND DAN WORK FLEXIBILITY TERHADAP KINERJA KARYAWAN PT. MANDIRI TUNAS FINANCE DENGAN ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL INTERVENING - Rina Maretasari; Dwi Ratmawati (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
Introduction: Leasing in Indonesia has taken part in corporate financing. Financing companies are also able to grow quite impressively so that they require a lot of manpower, especially in the sales (marketing) and also collection (collector) departments. This study aims to see how Job Demand and Job Flexibility are able to influence Organizational Commitment and ultimately affect employee performance in the marketing and collection departments.Methods: The sample used in this study were marketing and collection staff at PT. Mandiri Tunas Finance regional area 7 (covering branches Surabaya 1, Surabaya 2, Gresik, Mojokerto, Tuban, Madiun, Kediri, and Malang). The research used quantitative research methods with external and internal model calculations that included validity, reliability, and data analysis using Smart PLS2.0. The analysis technique used for all hypotheses is Partial Least Square.Results: Testing of marketing and collection staff at PT. Mandiri Tunas Finance in regional 7 produces: (1) Job Demand has a significant effect on Organizational Commitment. (2) Work Flexibility has a significant effect on Organizational Commitment. (3) Organizational Commitment has a significant effect on employee performance and mediates the relationship between Job Demand and Job Flexibility on employee performance.Conclusion and suggestion: The company is expected to be able to encourage employees to fulfill their job demands without reducing the performance of these employees